2012
DOI: 10.1017/s0261444811000498
|View full text |Cite
|
Sign up to set email alerts
|

Principles for code choice in the foreign language classroom: A focus on grammaring

Abstract: The social and cultural ‘turn’ in language education of recent years has helped move language teaching and curriculum design away from many of the more rigid dogmas of earlier generations, but the issue of the roles of the learners’ first language (L1) in language pedagogy and classroom interaction is far from settled. Some follow a strict ‘exclusive target language’ pedagogy, while others ‘resort to’ the use of the L1 for a variety of purposes (see ACTFL 2008). Underlying these competing views is the perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 21 publications
1
25
0
3
Order By: Relevance
“…Further research is needed to shed more light on potential effective functions of learners' L1. In fact, learners' L1 might serve a lot of pedagogical, discursive, and social functions just as any use of L2 does (Levine, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Further research is needed to shed more light on potential effective functions of learners' L1. In fact, learners' L1 might serve a lot of pedagogical, discursive, and social functions just as any use of L2 does (Levine, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies support Vygotsky's findings. Morahan (2010), for instance, found that when using the L1 sporadically in pair/group work, it assists learners to cognitively process the activity-at-hand at a higher level (also see Levine, 2014;Wells, 1999).…”
Section: International Perspectivementioning
confidence: 99%
“…Research on teachers' language use in second language (L2) classrooms has increased dramatically in number over the past 20 years, with studies looking at this issue from numerous perspectives (e.g. de la Campa & Nassaji, 2009;Lee, 2016;Lee & Macaro, 2013;Levine, 2003Levine, , 2011Levine, , 2014Macaro, 2001;Rolin-Ianziti & Brownlie, 2002;Rolin-Ianziti & Varshney, 2008;van der Meij & Zhao, 2010;Zhao & Macaro, 2016). One strand of this research has sought to measure the amount of the first language (L1) and L2 use on the part of teacher (e.g.…”
Section: Introductionmentioning
confidence: 99%